The thorn necklace : healing through writing and the creative process - Block, Francesca Lia (Seal Press, 2018)
An exploration of the writing life by Francesca Lia Block, offers visceral insights and healing exercises for the writer who creates as a way to process pain and adversity. Block offers guideposts of awareness for writers, such as how to find a muse, channeling agony into art, putting chaos into order, ignoring the inner critic, fostering personal perseverance, and thriving as an artist in a troubled world. The author also addresses the intrinsic value of channeling our experiences into the written word and provides compassionate support to the reader for his or her own write-to-heal process"--